2023
DOI: 10.21927/ijubi.v6i1.3275
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sentimen Pengguna Media Sosial Terhadap Aplikasi M-Health Peduli Lindungi Dengan Metode Lexicon Based Dan Naïve Bayes

Riky Iskandar Syah,
Hoiriyah Hoiriyah,
Miftahul Walid

Abstract: Pedulilindungi atau satusehat merupakan aplikasi yang dirilis secara resmi guna menangani penyebaran virus Covid-19 dan vaksinasi. Namun, dikarenakan suatu insiden besarnya kebocoran data pribadi, terutama identitas pribadi, kepercayaan masyarakat terhadap aplikasi tersebut sangat rendah. Untuk mengetahui pendapat masyarakat saat ini maka dilakukanlah penelitian dengan mengkombinasikan metode <em>Lexicon Based</em> dan <em>Na</em><em>ïve Bayes</em>. Hasil klasifikasi sentime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Ini menunjukkan bahwa gabungan algoritma Lexicon Based dan Naive Bayes kurang efektif dalam mengklasifikasikan data dari Twitter yang diambil menggunakan tweet-harvest. Hasil klasifikasi sentimen menunjukkan bahwa TikTok dan YouTube cenderung memiliki opini netral dari masyarakat, sementara Twitter didominasi oleh opini positif [10].…”
Section: Literature Reviewunclassified
“…Ini menunjukkan bahwa gabungan algoritma Lexicon Based dan Naive Bayes kurang efektif dalam mengklasifikasikan data dari Twitter yang diambil menggunakan tweet-harvest. Hasil klasifikasi sentimen menunjukkan bahwa TikTok dan YouTube cenderung memiliki opini netral dari masyarakat, sementara Twitter didominasi oleh opini positif [10].…”
Section: Literature Reviewunclassified
“…Metode Lexicon adalah metode yang melibatkan frasa, ungkapan, atau isi teks yang umumnya ditemukan dalam percakapan, dialog, pesan, ulasan, dan sejenisnya. Pendekatan Lexicon menggunakan daftar kata sentiment yang terdiri dari kata-kata positif, netral, dan negatif yang dikaitkan dengan kata-kata dalam kalimat untuk menentukan tingkat polaritasnya [11] Dalam kamus tersebut setiap kata telah diberikan skor polaritas yang berkisar dari -1 untuk kategori negatif hingga +1 untuk kategori positif [12]).…”
Section: Metode Lexiconunclassified
“…Research to analyze public opinion related to e-government use, predict public opinion related to e-government use, and analyze modeling topics related to e-government use has been carried out by several researchers [4, 3, 5-8, 2, 9] When a software product is used in a certain context, the interaction between humans and the program is related to the software quality (QinU). Additionally, sentiment analysis is used as a method to assess the caliber of application goods [9][10][11][12][13][14][15][16][17][18] one of them is e-government application product [7]. The main objective of the proposed sentiment analysis is to find out citizens' comments about being written in e-government environments and to improve the quality of e-services [3].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has indicated the efficacy of Naive Bayes algorithms in sentiment analysis for government applications, with diverse outcomes in terms of accuracy and methodology. Several research have examined the utilization of the Naive Bayes algorithm in the Mobile Alpukat and Sentuhh Tanahku applications [11], along with the deployment of the Support-vector-machine approach in the Jamsostek application [15]. Sentiment analysis research that uses different methods is Kuwait e-government with Logistic regression and the result Logistic regression [13], M-Health PeduliLindungi Application [14] with Lexicon-based and Naive Bayes Method and Mobile JKN [10] with Maximum Entropy and Mutual Information Selection.…”
Section: Introductionmentioning
confidence: 99%